Use of parenteral nutrition in the first postnatal week in England and Wales: an observational study using real-world data. Issue 1 (25th August 2022) - Webbe, James; Battersby, Cheryl; Longford, Nicholas; Oughham, Kayleigh; Uthaya, Sabita; Modi, Neena; Gale, Chris
Abstract : Background: Parenteral nutrition (PN) is used to provide supplemental support to neonates while enteral feeding is being established. PN is a high-cost intervention with beneficial and harmful effects. Internationally, there is substantial variation in how PN is used, and there are limited contemporary data describing use across Great Britain. Objective: To describe PN use in the first postnatal week in infants born and admitted to neonatal care in England, Scotland and Wales. Method: Data describing neonates admitted to National Health Service neonatal units between 1 January 2012 and 31 December 2017, extracted from routinely recorded data held the National Neonatal Research Database (NNRD); the denominator was live births, from Office for National Statistics. Results: Over the study period 62 145 neonates were given PN in the first postnatal week (1.4% of all live births); use was higher in more preterm neonates (76% of livebirths at <28 weeks, 0.2% of term livebirths) and in neonates with lower birth weight. 15% (9181/62145) of neonates given PN in the first postnatal week were born at term. There was geographic variation in PN administration: the proportion of live births given PN within neonatal regional networks ranged from 1.0% (95% CIs 1.0 to 1.0) to 2.8% (95% CI 2.7 to 2.9). Conclusions and relevance: Significant variation exists in neonatal PN use; it is unlikely this reflects optimal use of an expensive intervention. Research is needed to identify which babies will benefit most and which are at risk of harm from early PN. Trial registration number: ClinicalTrials.gov: NCT03767634 ; registration date: 6 December 2018.